Inclusão digital e gêneros digitais em cursos a distância - Pineda, Andréa Martini (2007)
With the intent of identifying possible relations between the digital inclusion and the use of digital genders, this study investigated how the process of digital lettering took place by part of the teachers from the state network that participated in a distant course, sponsored by PUC/SP in partnership with the State Education Board (Secretaria Estadual de Educação do Estado de São Paulo SEE/SP), during the March to June 2005 period. The theoretical basis emanated from the contexture of the Brazilian digital inclusion, and then to focus the question of defined genders through the Functional-Systemic Theory approach (Halliday, 1994), focusing especially on the genders potential structure (Hasan, 1985) and finally reverting to the digital genders (Machado, 2002). The literature and researched experiences showed that, to include any actor in the current scenario of the information and communication technology (and inhibit the digital exclusion), instrumental compact drills do not suffice or the connection promptness and access to equipment. It is necessary to consider the context and its preexisting needs and, then focus on digital lettering actions. Recognizing its multiplying potential, the participants of this research were teachers from the public network that, despite of being central agents in the course of the digital inclusion, are very little examined on researches covering the theme. The observed scenario was a distant prolonged graduation course on a on-line modality, by its character to democratize the information. The studied course was the Práticas de Leitura e Escrita na Contemporaneidade (Reading and Writing Practices in Contemporariness), by contemplating the digital lettering in its objectives. The applied corpus was composed by messages posted in two forums and the individual presentations written by the students. In this manner, this study articulates concepts and experiences in two main scopes: of the Information and Communication Technologies (TICs) and the Applied Linguistic. This research intends to foster a reflection about the teachers role in different contexts of digital inclusion and, in this manner, contribute with already existing projects and stimulate the establishment of new ones, addressed to this and other people in general